RECURRENT STENOSING LARYNGOTRACHEITIS AMONG CHILDREN: CLINICAL AND IMMUNOLOGIC PECULIARITIES, THERAPY OPPORTUNITIES - V.V. Karpov; M.G. Lukashevich; L.A. Safronenko; E.E. Makovkina; T.N. Surazakova ("Paediatrician" Publishers LLC, 2007)
Rehabilitation of the children with the recurrent stenosing laryngotracheitis (SLT) is still an urgent issue due to the pathogenesis heterogeneity of the recurrent croup cases, its clinical manifestations, effects of the applied therapy and uncertainty of the disease outcome. The article shows the peculiarities of the anamnesis and clinical symptoms of the recurrent SLT, vegetative reactivity and immune response within this category of patients. The authors stress the efficiency of the local antibacterial medication - fusafungine (bioparox) in treatment of the given disease. Key words: children, recurrent stenosing laryngotracheitis, vegetative reactivity, immunity, fusafungine.